Dietary recommendations for patients with nonalcoholic fatty liver disease - Kargulewicz, Angelika; Stankowiak-Kulpa, Hanna; Grzymisławski, Marian (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Changes to patients’ lifestyle, especially a modified dietary approach, play a key role in the treatment of nonalcoholic fatty liver disease (NAFLD). A balanced, limiting and individually tailored nutritional scheme enables weight loss and an improvement in the clinical picture of NAFLD. According to nutritional recommendations for patients with NAFLD, carbohydrates should comprise 40–50% of total dietary energy. It is advisable to increase the amount of complex carbohydrates rich in dietary fibre. A major role in the aetiology of NAFLD is played by excessive intake of fructose, which is related to the rise in consumption of nonalcoholic beverages among subjects in developed countries. Fat intake should comprise < 30% of daily calories. It is essential to increase consumption of food products rich in mono- and polyunsaturated fatty acids. Ingestion of protein should constitute 15–20% of total energy.